Listeria monocytogenes meningitis. Issue 6 (17th April 2018) - Matsuo, Takahiro; Mori, Nobuyoshi; Sakurai, Aki; Furukawa, Keiichi
Key Clinical Message: Tumbling motility is one of the useful characteristics of Listeria monocytogenes . This can be helpful to identify the causative pathogen along with Gram staining before the confirmatory microbiological examination. Abstract : Tumbling motility is one of the useful characteristics of Listeria monocytogenes . This can be helpful to identify the causative pathogen along with Gram staining before the confirmatory microbiological examination.